Analysis of wavelet transform de-noising technique based on measured lightning return stroke electric field - Arshad S.N.M.; Ab Kadir M.Z.A.; Izadi M.; Hamzah M.N.; Ariffen A.M.; Wooi C.L.; Anuar A. (American Institute of Physics Inc., 2023)
This paper presents a difference type of wavelet transform de-noising technique based on measured lightning electric field. The lightning electric fields captured by two parallel plats sensor and the signal were analyses accordingly. In engineering application, lightning stroke current parameter will relate with electric fields and these parameters can be recognized by direct and in-direct measuring method. Therefore, measuring lightning electric fields (LEF) using parallel plate was done by many researchers. However, measuring LEF has many disturbances such as noise from other apparatus and other device. Therefore, de-noising of LEF signal is important to get useful signal for further research. For this reason, the Centre for Electromagnetic and Lighting Protection Research (CELP) group has been working on a research program to study and characteristic lightning using de-noising technique in order to process and analyse the radiated LEF produced during flash happens. Only three types of wavelet transform are selected and there are Daubechies, Symlets and Coiflets wavelet. The result will be discussed and the best will be selected based on the measured signal. 2021 American Institute of Physics Inc.. All rights reserved.